Evidence for particle acceleration to the knee of the cosmic ray spectrum in Tycho's supernova remnant - Eriksen, Kristoffer A. (2011)
Supernova remnants (SNRs) have long been assumed to be the source of cosmic rays (CRs) up to the "knee" of the CR spectrum at 1015 eV, accelerating particles to relativistic energies in their blast waves by the process of diffusive shock acceleration (DSA). Since CR nuclei do not radiate efficiently, their presence must be inferred indirectly. Previous theoretical calculations and X-ray observations show that CR acceleration significantly modifies the structure of the SNR and greatly amplifies the interstellar magnetic field. We present new, deep X-ray observations of the remnant of Tycho's supernova (SN 1572, henceforth Tycho), which reveal a previously unknown, strikingly ordered pattern of non-thermal high-emissivity stripes in the projected interior of the remnant, with spacing that corresponds to the gyroradii of 1014-1015 eV protons. Spectroscopy of the stripes shows the plasma to be highly turbulent on the (smaller) scale of the Larmor radii of TeV energy electrons. Models of the shock amplification of magnetic fields produce structure on the scale of the gyroradius of the highest energy CRs present, but they do not predict the highly ordered pattern we observe. We interpret the stripes as evidence for acceleration of particles to near the knee of the CR spectrum in regions of enhanced magnetic turbulence, while the observed highly ordered pattern of these features provides a new challenge to models of DSA. © 2011. The American Astronomical Society.